Aetiology‐based clinical scenarios predict outcomes of transcatheter edge‐to‐edge tricuspid valve repair of functional tricuspid regurgitation. (29th July 2019) - Schlotter, Florian; Orban, Mathias; Rommel, Karl‐Philipp; Besler, Christian; von Roeder, Maximilian; Braun, Daniel; Unterhuber, Matthias; Borger, Michael; Hagl, Christian; Orban, Martin; Nabauer, Michael; Massberg, Steffen; et al.
Abstract : Aims: Transcatheter tricuspid valve repair (TTVR) is an emerging technique to treat tricuspid regurgitation (TR). Predictors of adverse outcomes are scarce, and stratification by TR aetiologies is lacking. Methods and results: We report the bi‐centre procedural outcomes of 164 patients undergoing TTVR for TR stratified into four aetiology‐based clinical scenarios (CSs). By stepwise categorization, patients were categorized into Dialysis‐CS if they were on chronic haemodialysis; patients not undergoing dialysis with MR grade ≥ 3 into MR‐CS; patients not meeting the inclusion into Dialysis‐CS or MR‐CS with an invasively‐determined systolic pulmonary artery pressure ≥ 50 mmHg into PAPs‐CS; and the remaining patients into Afib‐CS in case a history of atrial fibrillation/flutter existed. Clinical characteristics and procedural outcomes were evaluated. Procedural success was > 80% in all CSs and decreased mortality ( P  = 0.03). Within the group of patients with procedural success, PAPs‐CS had the highest rates of the primary endpoint of death, heart failure hospitalization or reintervention ( P  = 0.01). Mortality was significantly higher in PAPs‐CS when compared to the other CSs ( P  = 0.03) and Dialysis‐CS had the highest mortality rate (33.3%). In all CSs, the majority of patients experienced New York Heart Association functional class improvement at follow‐up. Conclusions: Stratification of TTVR into aetiology‐based CSs may open new paths to stratify for clinical risk and procedural benefit and may aid in the design of clinical trials in the heterogeneous TTVR patient population. Despite the observed CS outcome differences, TTVR appears feasible and safe, and confers functional improvements in patients with TR and heart failure.